Penerapan Pembelajaran Kooperatif Tipeteam Games Tournment (TGT)Untuk Meningkatkan Aktivitas Belajarmatematika Siswa Kelas VIII MTs YPKS Padangsidimpuan - Hasibuan, Siti Gabena; Nova Christina Dewi; Nurdalilah (Program Studi Matematika Universitas Graha Nusantara Padangsidimpuan, 2023)
This research aims to determine the increase in student learning activities with Team Games Tournament (TGT) type cooperative learning at MTs YPKS Padangsidimpuan. This type of research is classroom action research. The object of this research is to increase student learning activities through TGT type cooperative learning in class VIII MTs YPKS Padangsidimpuan. The research subjects were 33 students in class VIII-4. /friend's explanation was 18%, the activity of reading student books/LKS was 2.5%, the activity of noting the explanation of the teacher/friend/from the book was 12%. , distribution activities by 16%, and activities that are not relevant to learning by 51%. So it was found that student activities for each activity category had not yet reached the ideal activity criteria. The results of the analysis after being given action II were from the results of observing the activity of listening/paying attention to the teacher/friend's explanation by 46%, the activity of reading student books/LKS by 7.5%, the activity of noting the teacher/friend's explanation/from the book by 10.5%, the activity division was 19%, and activities that were not relevant to learning were 17%. This shows that student activities for the four activity categories have experienced improvement, but have met the ideal activity criteria